Is Russia sick with Dutch Disease? - Abdullaeva, Nadiia; Máslo, Lukáš Augustin, 1985-; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
The aim of this work is to prove a hypothesis whether Russia is sick with Dutch disease or not. In the theoretical part, the author expounds the model of Dutch disease by Corden, Neary (1982) and places the phenomenon into a historical perspective. Further on, the author identifies four main symptoms of the Dutch disease, i. e. an increasing dependence of a country on the export of natural resources, appreciation of the real exchange rate, a decline of the manufacturing sector and a growth of the service sector and, finally, an overall wage growth. In the empirical part, the author tests the presence of the particular symptoms of the Dutch disease in the Russian economy on the data set for the years 1998-2015, drawing upon the research of Oomes, Kalcheva (2007) and extending it by adding the symptom of increasing dependence of a country on the export of natural resources (the 1st symptom) and by prolonging the time series until 2015. The author presents her own multiple regression model with the dependent variable of real effective exchange rate and independent variables interest rate, oil prices and government expenditures, proving a positive correlation of 83% between the real effective exchange rate and oil price. Next, the author proves that the service sector and the natural resource sector increased their respective shares of the GDP in the economy by 6 and 5 percentage points between 2000-2015, while the manufacturing sector decreased almost by the 9 percentage points. By this, the author supports the assumption about the ongoing indirect deindustrialization process and, in effect, supports her assumption about the presence of the third symptom.
Vedoucí práce: Lukáš Máslo
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses